Christians, Muslims and the State in Twentieth-Century Egypt and Indonesia - Stanley, Brian (Studies in church history, 2015)
Surveys of the historical relationship between Christianity and other faiths often suggest that through a process of theological enlightenment the churches have moved from crusade to cooperation and from diatribe to dialogue. This trajectory is most marked in studies of Christian-Muslim relations, overshadowed as they are by the legacy of the Crusades. Hugh Goddard’s A History of Christian-Muslim Relations proceeds from a focus on the frequently confrontational inter-communal relations of earlier periods to attempts by Western theologians over the last two centuries to define a more irenic stance towards Islam.1 For liberal-minded Western Christians this is an attractive thesis: who would not wish to assert that we have left bigotry and antagonism behind, and moved on to stances of mutual respect and tolerance? However laudable the concern to promote harmonious intercommunal relations today, dangers arise from trawling the oceans of history in order to catch in our nets only those episodes that will be most morally edifying for the present. What Herbert Butterfield famously labelled ‘the Whig interpretation of history’ is not irrelevant to the history of interreligious relations. In this essay I shall use the experience of Christian communities in twentieth-century Egypt and Indonesia to argue that the determinative influences on Christian-Muslim relations in the modern world have not been the progressive liberalization of stances among academic theologians but rather the changing views taken by governments in Muslim majority states towards both their majority and minority religious communities. Questions of the balance of power, and of the territorial integrity of the state, have affected Christian Muslim relations more deeply than questions of religious truth and concerns for interreligious dialogue.